USE OF MODERN PEDAGOGICAL TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Shakhnoza Mashrabovna Mukhtarova (Western European Studies, 2024)
In the article, the organization of modern education, the methods of using various interactive methods in mother tongue classes, the delivery of certain theoretical knowledge to students in a short time by using advanced pedagogical technologies, and the formation of competencies and skills in certain activities. it is about doing, monitoring the activities of students, evaluating the level of knowledge, skills and abilities acquired by them.
Keywords: pedagogical technology; educational methods